Single-cell protein-DNA interactomics and multiomics tools for deciphering genome regulation - Xiong Haiqing; Wang Runyu; He Aibin (National Science Open, 2023)
The emergence of single-cell genomic and transcriptomic sequencing accelerates the development of single-cell epigenomic technologies, providing an unprecedented opportunity for decoding cell fate decisions largely encoded in the epigenome. Recent advances in single-cell multimodality epigenomic technologies facilitate directly interrogating the regulatory relationship between multi-layer molecular information in the same cell. In this review, we discuss recent progress in development of single-cell multimodality epigenomic technologies and applications in elucidating cellular diversifications in development and diseases, with a focus on protein-DNA interactomics and regulatory links between epigenome and transcriptome. Further, we provide perspective on the future direction of single-cell multiomics tool development as well as challenges facing ahead.